Fabrication of double layers of aramid fiber/alumina/epoxy resin laminate composite using low-pressure technique - W. Nhuapeng (2018)
An experimental investigation was carried out to study the fabrication of double layers of aramid fiber/alumina/epoxy resin laminate composites using low-pressure technique. To obtain the sample with high wear resistance property, the micron size of alumina particles were added into epoxy resin using the ultrasonic processor. The physical and mechanical properties such as density, hardness, impact test, wear resistance and tensile strength of the composites samples were investigated. Furthermore, microstructures of specimens were also examined by scanning electron microscope (SEM). From the results, it was found that the mechanical properties of double layers laminate composites of aramid fiber/alumina/epoxy resin could improve by using the low-pressure technique. © 2008 Trans Tech Publications, Switzerland.